The Works of Edgar Allan Poe $1 (BVolume 3s - Poe, Edgar Allan, 1809-1849 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Works of Edgar Allan Poe $1 (BVolume 3" by Edgar Allan Poe is a collection of narratives and short stories likely compiled during the mid-19th century. This volume includes significant works such as "Narrative of A. Gordon Pym," which introduces the titular character whose adventures at sea encompass themes of exploration, danger, and survival. The narrative intertwines fictional elements with the real-life experiences of its characters, inviting readers into a richly imaginative and suspenseful world. The beginning of this volume presents an introductory note by Arthur Gordon Pym detailing his extraordinary adventures in the South Seas, which prompted him to share his story. Pym recounts his upbringing and relationships, particularly with his friend Augustus Barnard, which sets the stage for their eventual ill-fated expedition at sea. Their reckless decision to sail out on a cold night leads to chaos when Barnard descends into intoxication, leaving Pym to manage their dangerously unsound vessel alone. The opening climaxes with a dramatic encounter that highlights the perils of their venture, ending with Pym's miraculous rescue after a harrowing sequence of events, laying the groundwork for further adventures to come. (This is an automatically generated summary.)s
Narrative of A. Gordon Pym -- Ligeia -- Morella -- A tale of the Ragged Mountains -- The spectacles -- King Pest -- Three Sundays in a week.
Release date is 2000-04-01
Produced by David Widger
Keywords: Fantasy fiction; Horror tales, American; American fiction -- 19th century